2015
DOI: 10.1016/j.esp.2015.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Announcing one's work in PhD theses in computer science: A comparison of Move 3 in literature reviews written in English L1, English L2 and Spanish L1

Abstract: In this paper I explore cross-linguistic rhetorical variation in the Literature Review chapters of 30 doctoral theses of computer science written by English L1 (EngL1), Spanish L1 (SpaL1) and English L2 (EngL2) writers. Using Kwan's (2006) genreanalytical framework (Move 1: Establishing one part of the territory of one's own research; Move 2: Creating a niche; Move 3: Occupying the research niche), I particularly examine how writers present their research in Move 3 (M3). The results show the functional importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…They have been the focus of much attention in the study of genres, particularly research articles (e.g., Kanoksilapatham, 2013) and their part-genres (e.g. introductions (Cortes, 2013); literature reviews (Soler-Monreal, 2015); methods sections (Cotos et al, 2017), results and discussions sections (Le & Harrington, 2015), and research article abstracts (Omidian et al, 2018)). A similar but less frequent focus on lexical bun-| Research Papers dles has also appeared in studies of student research genres (e.g., see Durrant & Mathews-Aydinli, 2011;Durrant, 2017).…”
Section: Connecting Rhetorical Moves With Theirmentioning
confidence: 99%
“…They have been the focus of much attention in the study of genres, particularly research articles (e.g., Kanoksilapatham, 2013) and their part-genres (e.g. introductions (Cortes, 2013); literature reviews (Soler-Monreal, 2015); methods sections (Cotos et al, 2017), results and discussions sections (Le & Harrington, 2015), and research article abstracts (Omidian et al, 2018)). A similar but less frequent focus on lexical bun-| Research Papers dles has also appeared in studies of student research genres (e.g., see Durrant & Mathews-Aydinli, 2011;Durrant, 2017).…”
Section: Connecting Rhetorical Moves With Theirmentioning
confidence: 99%
“…Following Kwan and chan (2014), the current study examines source ideas cited in specific moves/steps in LRs in Information Systems RAs by drawing on their citation classification scheme as well as the widely-established cARS model (Swales, 1990) originally postulated for RA Introductions but subsequently found applicable to LRs in theses and RAs (Kwan, 2006;Kwan et al, 2012;Gil-Salom & Soler-Monreal, 2014;Soler-Monreal, 2015;Tessuto, 2015;Tseng, 2018).…”
Section: Textmentioning
confidence: 99%
“…Previous research has demonstrated the effect of socio-cultural factors on the written product of non-native speakers (e.g., Ahmadi, 2022;Marefat & Mohammadzadeh, 2013;Moreno, 2021;Tahririan & Jalilifar, 2004). That said, most cross-cultural, genre-based studies have focused on abstract (e.g., Kafes, 2015;Marefat & Mohammadzadeh, 2013;Samar et al, 2014;Tankó, 2017) and introduction sections (e.g., Del Saz Rubio, 2011;Lu et al, 2021;Soler-Monreal, 2015). Little evidence is available about comparative, cross-cultural, genre-based studies on the discussion sections of applied linguistics RAs written by NES and Persian native speakers as NNES, thus calling for further research.…”
Section: Introductionmentioning
confidence: 99%